Neutrophil-to-Lymphocyte Ratio Predicts Intravenous Immunoglobulin-Resistance in Infants Under 12-Months Old With Kawasaki Disease - Chen, Yongbing; Hua, Ying; Zhang, Chunyu; Chen, Selena; Zhang, Qingyou; Liao, Ying; Yan, Hui; Wang, Yuli; Liu, Ping; Qi, Jianguang; Liu, Xueqin; Chen, Yonghong; et al. (Frontiers in Pediatrics, 2019)
Objective: We evaluated the ability of peripheral blood neutrophil-to-lymphocyte ratio (NLR) to predict the intravenous immunoglobulin (IVIG) resistance in Kawasaki disease (KD) patients under 1 year of age. Methods: A total of 92 KD patients under the age of 1 year and who were hospitalized in Peking University First Hospital from June 2007 to August 2016 were recruited in this study. The clinical and laboratory data were analyzed to see if peripheral blood NLR was useful for predicting the IVIG-resistance in KD. Results: Totally 81 out of 92 patients were IVIG responders while 11 resistant to IVIG, with no significant difference in age, gender, ratio of the number of the incomplete and the number of complete KD, and the number of patients with coronary artery lesion between two groups (p>0.05). Peripheral blood NLR was increased significantly in IVIG-resistant children compared to the IVIG responders [2.6 (interquartile range: 1.4, 3.8) vs 1.7 (interquartile range: 0.9, 2.3), p=0.039]. A cut-off value of NLR of 2.51 in KD patients younger than 1-year old yielded a sensitivity of 0.545 and specificity of 0.840, respectively, in the prediction of IVIG resistance. An area under the curve of 0.692 (95% confidence interval 0.526-0.859, p=0.039) was determined. Conclusions: The peripheral blood NLR≥2.51 is useful to predict the IVIG resistance in KD patients younger than 1-year old.